The Influence of Brand Ambassador, Website Quality, and E-WOM on Purchase Decisions in Shopee E-Commerce within the Special Region of Yogyakarta - Hafizh, Haidar Andi; Liestyana, Yuli (CV. Strata Persada Academia, 2025)
This study aims to examine the influence of brand ambassador, website quality, and electronic word of mouth (E-WOM) on purchase decisions in Shopee e-commerce within the Special Region of Yogyakarta. Employing a quantitative survey approach, data were collected from 100 active Shopee users through purposive sampling, using structured questionnaires measured on a five-point Likert scale. The collected data were analyzed using multiple linear regression with SPSS version 23 to determine both partial and simultaneous effects among variables. The findings reveal that brand ambassador, website quality, and E-WOM each have a positive and significant impact on purchase decisions. Specifically, effective brand ambassadors enhance consumer trust and brand image, while a high-quality website with appealing visuals, easy navigation, and security features fosters user confidence and satisfaction. Likewise, positive E-WOM through online reviews and peer recommendations significantly strengthens consumer purchase intentions. These findings underscore the importance of integrating digital marketing communication strategies to enhance customer experience and loyalty in e-commerce. Future research is recommended to incorporate additional variables such as brand trust, customer satisfaction, and digital service quality to develop a more comprehensive model of online consumer behavior.